Ответ:
Пошаговое объяснение:
1.
2x+7=5x+13
2x-5x=13-7
-3x=6
x=6/(-3)=-2
2.
3x-23=19-4x
3x+4x=19+23
7x=42
x=42/7=6
3.
1,3x+4,8=2,9x-7,2
1,3x-2,9x=-7,2-4,8
-1,6x=-12
x=(-12)/(-1,6)=120/16=30/4=7,5
4.
![\frac{4}{7}x+1\frac{3}{7}=\frac{6}{7}x-5\frac{5}{7}\\\frac{4}{7}x-\frac{6}{7}x=-5\frac{5}{7}-1\frac{3}{7}\\-\frac{2}{7}x=-7\frac{1}{7}=-\frac{50}{7}\\2x=50\\x=25 \frac{4}{7}x+1\frac{3}{7}=\frac{6}{7}x-5\frac{5}{7}\\\frac{4}{7}x-\frac{6}{7}x=-5\frac{5}{7}-1\frac{3}{7}\\-\frac{2}{7}x=-7\frac{1}{7}=-\frac{50}{7}\\2x=50\\x=25](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B7%7Dx%2B1%5Cfrac%7B3%7D%7B7%7D%3D%5Cfrac%7B6%7D%7B7%7Dx-5%5Cfrac%7B5%7D%7B7%7D%5C%5C%5Cfrac%7B4%7D%7B7%7Dx-%5Cfrac%7B6%7D%7B7%7Dx%3D-5%5Cfrac%7B5%7D%7B7%7D-1%5Cfrac%7B3%7D%7B7%7D%5C%5C-%5Cfrac%7B2%7D%7B7%7Dx%3D-7%5Cfrac%7B1%7D%7B7%7D%3D-%5Cfrac%7B50%7D%7B7%7D%5C%5C2x%3D50%5C%5Cx%3D25)
5.
2(x-3)-4(x+1)=5x-38
2x-6-4x-4=5x-38
2x-4x-5x=-38+6+4
-7x=-28
x=(-28)/(-7)=4